STRATEGIC INTEGRATION OF GASTRONOMIC HERITAGE IN GREEN TOURISM: AN EMPIRICAL STUDY FROM SERBIA - MILUTINOVIĆ, Andrija; PANTOVIĆ, Danijela; BUGARČIĆ, Jovan (Journal of process management and new technologies, 2026)
Traditional gastronomy is an important part of intangible cultural heritage and plays an increasingly important role in the development of sustainable tourism. Bearing in mind the rise of interest in environmentally friendly tourism, traditional gastronomy may add to the ecological, socio-cultural, and economic sustainability of tourism destinations. In addition to cultural significance, traditional food products may also influence tourists’ attitudes toward environmentally friendly tourism. This study aims to investigate the role of traditional gastronomy in the green transition of tourism in the Republic of Serbia, with particular emphasis on tourists’ perceptions and intentions. A quantitative research approach, based on a structured survey of 95 tourists who have previously consumed traditional gastronomic products at various tourism destinations in the Republic of Serbia, was used. The respondents rated 32 items on a seven-point Likert scale. The results indicated high reliability since the internal consistency reliability coefficient for the instrument was high, with Cronbach’s alpha = 0.961. Descriptive analysis and Spearman’s rank correlation method were used to determine the relationship between gastronomic motivation factors and tourists’ intentions on green tourism. The results indicated a statistically significant positive relationship between gastronomic motivation factors and tourists’ intentions. This suggests that traditional gastronomy could be a major influence on tourists’ attitudes towards green tourism. Therefore, it shows the importance of incorporating gastronomic heritage in green tourism.
Keywords: Traditional gastronomy; green tourism; sustainable development; gastronomic heritage; Republic of Serbia